Re-evaluating pervasive academic exclusion in South African higher education institutions: Challenging the norm(alised) - Ravhuhali, F.; Mboweni, H. F. (South African Journal of Higher Education, 2024)
The pervasive issue of academic exclusion within South African higher education institutions is a deeply concerning matter. This phenomenon has resulted in a significant number of students prematurely discontinuing their degree programmes. In this article, we argue that academic exclusion remains largely unchallenged and has been normalised, despite its far-reaching implications, and therefore needs to be re-evaluated. Our inquiry centres on two key questions: What are the underlying reasons for academic exclusion in higher education, and how are these exclusion rules communicated to students, taking into account the support they receive? These questions serve as a foundation for a critical examination of the current state of academic exclusion and the proposal of alternative approaches to supporting academically struggling students throughout their educational journey. Drawing on Nancy Fraser’s concept of the participation parity framework, this qualitative study employed a combination of desktop research and open-ended questionnaires to collect data from six excluded students. Content and thematic analyses are employed to analyse the collected data. The study’s findings highlight the inadequacy of current support mechanisms for students and the diverse, often unplanned paths they contemplate after exclusion. Given this, the article advances and, therefore, instigates the conversations on and accentuates the importance of re-evaluating and revising academic exclusion policies within higher education institutions. It argues that students should receive comprehensive support throughout their academic journey and throughout their career trajectories within these institutions. While this study seeks to initiate round-the-table discussions on academic exclusion rules and re-evaluation thereof, it calls for further system-wide research to explore mechanisms for supporting academically challenged students before they face academic exclusion, and to delve deeper into this critical issue’s impact on students, their families, society, the economy, and related areas within higher education institutions.